BRANDING STRATEGY TO INCREASE INTEREST IN VISITING USERS - Sari, Shinta Nofita; Harefa, Hilda Syaf’aini (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
Currently, the public does not have a good perception of libraries. The public still considers libraries to be just old buildings that store old books, there are still people who do not understand the role of libraries as scientific institutions. Many people lack awareness of the role of libraries so they are reluctant to use library services. Therefore, libraries need to do branding so that the public can understand the unique value and role of libraries well. This study aims to determine whether branding positioning has an effect on increasing interest in visiting, branding personality has an effect on increasing interest in visiting, branding identity has an effect on increasing interest in visiting, branding communications has an effect on increasing interest in visiting, and branding positioning, branding personality, branding identity and branding communications simultaneously have an effect on increasing interest in visiting visitors at the Bung Hatta Proklamator Library, Bukit Tinggi. This type of research is quantitative descriptive. The population in this study is the number of visitors who visited in 2023 totaling 190,178 people. The sample in this study was 100 respondents using the Sample Random Sampling technique. The data analysis methods used are Instrument Test, Classical Assumption Test, Multiple Linear Regression Test and Hypothesis Test using SPSS Version 24 for Windows. The results of the study indicate that branding positioning has an effect on increasing interest in visiting, branding personality has an effect on increasing interest in visiting, branding identity has an effect on increasing interest in visiting, branding communications has an effect on increasing interest in visiting, and branding positioning, branding personality, branding identity and branding communications simultaneously have an effect on increasing interest in visiting